Analisis Diskursus Kebijakan Vasektomi sebagai Prasyarat Bantuan Sosial: Studi Komparatif Perspektif Pragmatisme Politik dan Normatif Religius - Pratama, Wahyu Aji; M. Saeful Amri (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2025)
The vasectomy controversy as a prerequisite for social assistance triggered by the statement of West Java Governor Dedi Mulyadi has caused a debate between pragmatic and religious perspectives in Indonesia. This study aims to analyze the construction of the pro-con arguments for vasectomy through the debate between Adi Armando and K.H.Kholil Nafis at the